Inovasi Pojok Baca Digital Dalam Meningkatan Literasi Masyarakat Di Perpustakaan Kabupaten Probolinggo - Septiandika, Verto; Lestari, Maulidia Gita; Aisyah, Siti; Hidayatullah, M. Rizky; Amrullah, Muhammad Januar (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
This research aims to increase interest in reading and literacy in the community of Probolinggo Regency which is still quite low. The research method used is descriptive qualitative research method and seeks the necessary data by using library techniques and field research consisting of observations and interviews with the Head of Development Services. The results of this research were obtained several roles of the Digital Reading Corner (POCADI) in Increasing Public Interest in Reading, namely increasing literacy and making it easier to get information. So that some of the efforts made by the Regional Library of Probolinggo Regency in Growing Community Interest in Reading are providing outreach to the community, collaborating with schools and promoting through traveling fairy tales, and providing adequate facilities and infrastructure.